2021
DOI: 10.26434/chemrxiv-2021-mkt6v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electronic structure of NdO via slow photoelectron velocity-map imaging spectroscopy of NdO¯

Abstract: Electronically excited NdO is a possible product of the chemistry associated with the release of Nd into the ionosphere, and emission from these states may contribute to the observations following such experiments. To better characterize the energetics and spectroscopy of NdO, we report a combined experimental and theoretical study using slow photoelectron velocity-map imaging spectroscopy of cryogenically cooled NdO¯ anions (cryo-SEVI) supplemented by wavefunction-based quantum-chemical calculations. Using cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Therefore, it is necessary to use complex-valued wave functions in order to perform single-reference coupled-cluster calculations for such open-shell electronic states even for the scalar-relativistic calculations. This has been demonstrated in a recent study of NdO and NdO + , 75 which are valence isoelectronic to UO and UO + , respectively. In principle, an additivity scheme can be designed combining scalar-relativistic coupled-cluster calculations using complex-valued wave functions with spin−orbit corrections.…”
Section: Targeted Thermochemical Parameters Andmentioning
confidence: 52%
“…Therefore, it is necessary to use complex-valued wave functions in order to perform single-reference coupled-cluster calculations for such open-shell electronic states even for the scalar-relativistic calculations. This has been demonstrated in a recent study of NdO and NdO + , 75 which are valence isoelectronic to UO and UO + , respectively. In principle, an additivity scheme can be designed combining scalar-relativistic coupled-cluster calculations using complex-valued wave functions with spin−orbit corrections.…”
Section: Targeted Thermochemical Parameters Andmentioning
confidence: 52%
“…The absolute uncertainties are 0.1 cm −1 . In their SEVI study, Babin et al 16 found 10 bands of NdO with internal energies above 10,000 cm −1 that could be correlated with transitions observed by means of optical spectroscopy. None of these assigned upper states were more than 16,800 cm −1 above the NdO X(1)4 v″ =0 level.…”
Section: The Journal Ofmentioning
confidence: 80%
“…Kaledin 27 further developed the LFT model, calculating the term energies and leading electronic configurations of NdO states up to 3 eV. Ab initio calculations for the low energy excited states (<1 eV) have been reported by Krauss and Stevens, 28 Allouche et al, 29 and Babin et al 16…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations